University Education with Social Skills and Socio-Formative Approach - Yudelly Torrejón Rodríguez,; Elena Vega Torres,; Nely Yolanda Silva Fernández,; Melva Isabel Torres Donayre,; Wagner Colmenares Mayanga,; Rocío Isabel Ramírez Miguel,; Urfiles Bustamante Quiroz, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article examines the implementation of socio-formative strategies in university education to strengthen social skills and socio-emotional abilities. Based on theoretical frameworks such as Vygotsky's sociocultural theory, Bruner's discovery learning, and Morin's complexity theory, the study analyzes how these approaches contribute to addressing the challenges faced in higher education, especially during periods of uncertainty like the COVID-19 pandemic. The research highlights the role of social and emotional competencies in fostering integral development, adaptability, and critical thinking among students. Furthermore, the paper emphasizes the importance of aligning academic practices with socio-formative approaches to bridge the gap between academic and socio-emotional education, promoting sustainable and transformative learning experiences. The findings underscore the relevance of socio-formative strategies in preparing students for personal and professional success, as well as in fostering a knowledge-based and value-driven society.